(untitled) (Research, Society and Development, 2022)
Since the records of the new coronavirus spawn (SARS-CoV) in China in 2019, the process of increasing variants (Alpha, Gamma, beta and Delta) and complications as result such as coinfection, a situation in which a virus and a group of fungi or bacteria act concomitantly, further complicating the patient’s health status. The aim of this paper is to present the cardiorespiratory implications, by co-infection with bacteria, in patients diagnosed with COVID-19. This is a study characterized by an Integrative literature review. An amount of 127 articles were located from the advanced search and 05 articles were selected. As inclusion criteria we selected journals published between 2020 and 2021 in Portuguese and English, on the following databases: PubMed, Cochrane Library and Science Direct. As ineligibility criteria, we excluded manuscripts that did not comply with the objective and guiding question, monographs, dissertations and theses, editorial letters, and paid articles. Through the analysis of the presented references, we verified a high incidence of co-infection cases, which is one of the factors that aggravate patients with COVID-19. However, due to the shortage of literature, further studies are necessary to deepen the subject.